2016
DOI: 10.1016/j.tjog.2016.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of familial transmission of 17q12 microduplication associated with no apparent phenotypic abnormality

Abstract: The 17q12 microduplication may present with variable phenotypes including no apparent phenotypic abnormality in familial cases. However, neuropsychiatry assessment and monitoring should be warranted in childhood and through adulthood under such a circumstance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…These data suggest that mild ventriculomegaly and agenesis of the corpus callosum in the fetal ultrasound phenotype may also be indicators of the 17q12 microduplication syndrome. In contrast, Chen et al had reported the absence of obvious ultrasound abnormalities in a fetus with the 17q12 microduplication syndrome (26). This is in accordance to the normal ultrasound phenotype we observed in our study.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These data suggest that mild ventriculomegaly and agenesis of the corpus callosum in the fetal ultrasound phenotype may also be indicators of the 17q12 microduplication syndrome. In contrast, Chen et al had reported the absence of obvious ultrasound abnormalities in a fetus with the 17q12 microduplication syndrome (26). This is in accordance to the normal ultrasound phenotype we observed in our study.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the microduplication region was found to contain 15 OMIM genes, including HNF1B (189907), LHX1 (601999), CCL4L1 (603782), CCL4L2 (610757), and CCL3L1 (601395), among which HNF1B is the most closely related to the disease ( 26 31 ). The HNF1B gene is mostly associated with kidney disorders, followed by neurodevelopmental disorders ( 18 , 32 34 ).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The clinical features include renal cysts, diabetes of the young type 5(MODY5) [57], Mullerian aplasia, dysgenesis [8, 9], autism spectrum disorder schizophrenia [10, 11], learning difficulties, speech delay, neonatal cholestasis, and transient neonatal hypercalcemia [12]. The main clinical manifestations of chromosome 17q12 microduplication syndrome (OMIM 614526) are developmental delay, brain dysplasia, epilepsy, cognitive impairment, and behavioral abnormalities [13]. Less common phenotypes include esophageal atresia, eye abnormalities, cleft palate, heart defects, and sex reversal [14].…”
Section: Introductionmentioning
confidence: 99%